Subclass of k-uniformly starlike functions defined by symmetric q-derivative operator - Altinkaya, S.; Kanas, S.; Yal¸cin, S. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
The theory of q-analogs is frequently encountered in numerous areas, including fractals and dynamical systems. The q-derivatives and q-integrals play an important role in the study of q-deformed quantum-mechanical simple harmonic oscillators. We define a symmetric q-derivative operator and study a new family of univalent functions defined by using this operator. We establish some new relations between the functions satisfying analytic conditions related to conical sections.